Detection of Atypical Porcine Pestivirus in Piglets from Danish Sow Herds - Kasper Pedersen; Charlotte Sonne Kristensen; Bertel Strandbygaard; Anette Bøtner; Thomas Bruun Rasmussen (Viruses, 2021)
Atypical porcine pestivirus (APPV) was first discovered in North America in 2015 and was later shown to be associated with congenital tremor (CT) in piglets. CT is an occasional challenge in some Danish sow herds. Therefore, we initiated an observational case control study to clarify a possible relationship between CT and APPV in Danish pig production. Blood samples were collected from piglets affected by CT (n = 55) in ten different sow herds and from healthy piglets in five sow herds without a history of CT piglets (n = 25), as well as one sow herd with a sporadic occurrence of CT (n = 5). APPV was detected by RT-qPCR in all samples from piglets affected by CT and in three out of five samples from piglets in the herd with a sporadic occurrence of CT. In the herds without a history of CT, only one out of 25 piglets were positive for APPV. In addition, farmers or veterinarians in CT-affected herds were asked about their experience of the issue. CT is most often seen in gilt litters, and a substantial increase in pre-weaning mortality is only observed in severe cases. According to our investigations, APPV is a common finding in piglets suffering from CT in Denmark.